Value addition to carbon obtained from biosludge - Chua, Tiru Wei Lee (Nanyang Technological University, 2022)
In this paper, incorporation of carbon like powders obtained from biosludge into either metakaolin or silica fume geopolymers will be studied to be used as non-load bearing partition walls. Metakaolin displayed superior compressive strength and better workability with the addition of 0.5 wt.% of fibres as compared to the silica fume geopolymer samples. Therefore, the addition of the carbon like powders will be focused on the metakaolin based geopolymers. The compression strength of the metakaolin sample with the addition of 50 wt.% of carbon-like powder remains to be unaffected by the absorption of water. An attempt of reducing the density of the metakaolin-carbon composite was unsuccessful based on the XRF and density measurements. Ball milling was performed instead to increase the surface area of the carbon like powders to obtain a geopolymer composite with higher compressive strength. Based on the compression test, metakaolin samples containing the ball-milled powder had higher compressive strength as compared to the samples containing the baseline carbon powders.